2020
DOI: 10.1016/j.ifset.2020.102427
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Listeria monocytogenes in raw and hot smoked trout fillets by high hydrostatic pressure processing combined with liquid smoke and freezing

Abstract: Inactivation of Listeria monocytogenes in raw and hot smoked trout fillets by high hydrostatic pressure processing combined with liquid smoke and freezing. Innovative Food Science & Emerging Technologies, 64. 102427.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 72 publications
3
24
0
2
Order By: Relevance
“…The authors suggested that a homogeneous temperature within the sample achieved by an initial temperature that was low enough to keep the sample temperature below the melting point during compression, and the completion of melting within the holding time were necessary to take the advantage of combined subzero temperature and high pressure during pressure-assisted thawing. Ekonomou, Bulut, Karatzas, and Boziaris (2020) investigated the possibility of using a very low pressure in combination with liquid smoke and freezing to eliminate Listeria monocytogenes 10403S in trout samples. Treatment with liquid smoke followed by freezing prior to pressurization at 200 MPa for 15 min reduced the number of L. monocytogenes by more than 5-log CFU•ml -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that a homogeneous temperature within the sample achieved by an initial temperature that was low enough to keep the sample temperature below the melting point during compression, and the completion of melting within the holding time were necessary to take the advantage of combined subzero temperature and high pressure during pressure-assisted thawing. Ekonomou, Bulut, Karatzas, and Boziaris (2020) investigated the possibility of using a very low pressure in combination with liquid smoke and freezing to eliminate Listeria monocytogenes 10403S in trout samples. Treatment with liquid smoke followed by freezing prior to pressurization at 200 MPa for 15 min reduced the number of L. monocytogenes by more than 5-log CFU•ml -1 .…”
Section: Introductionmentioning
confidence: 99%
“…When cold-smoked salmon fillets were treated with HHP at 600 MPa for 120 s in combination with nisin (10 µg/g) it resulted in 3.99 log CFU/g reduction in L. innocua, without any apparent synergistic effect [73]. Ekonomou et al (2020) [28] investigated the synergistic effect of HHP at 200 MPa (15 min) with liquid smoke extracts and freezing and resulted in a more than 5-log reduction in CFU/g of the inoculated L. monocytogenes strain on the surface of hot smoked trout fillet.…”
Section: Microbiological Quality and Safetymentioning
confidence: 99%
“…In recent years, HP's treatment efficacy on bacterial inactivation has been extensively studied [25][26][27][28]. The degree of inactivation depends on the type of microorganism and their growth phase, the pressure level, the process temperature, and time (PTM), including the food or lab medium's pH and composition.…”
Section: High Hydrostatic Pressure-hhp 21 General Description Of Hhmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, el uso de tecnologías de barreras en filetes de trucha, que involucran el ahumado en caliente y congelación como operaciones previas al uso de alta presión hidrostática, demostró un efecto sinérgico. Así, la combinación de 0,5 % (v/v) de humo líquido, congelación (-80°C) y una presurización a 200 MPa por 15 minutos logró la reducción de Listeria monocytogenes en 5,48 log ufc/g (Ekonomou et al, 2020).…”
Section: Proceso De Ahumadounclassified